C. PROVANZA, P. EZKIAGA. Mahats-denboran.: Autoedizioa. Zarautz, 2004. 101 orrialde. - Otxoteko, Pello (EGAN, 2021)
PELLO OTXOTEKO. C. PROVANZA, P. EZKIAGA. Mahats-denboran. Autoedizioa. Zarautz, 2004. 101 orrialde.